O arquétipo do sagrado feminino e seus desdobramentos nas líricas de Arriete Vilela e Maria Teresa Horta: inconsonâncias e convergências - Schmidt, Clarice Braatz (2024)
This doctoral thesis aims to establish how the theme of the sacred feminine is structured in the works of the poets Arriete Vilela and Maria Teresa Horta to prove the unfolding of this motto, as well as the inconsistencies and convergences related to the subject when comparing the poetic work of these writers. The research was carried out through bibliographical research, using as a corpus the works Poesia Reunida (2009) by Maria Teresa Horta and Obra Poética Reunida (2010) by Arriete Vilela, basing the theoretical considerations and analysis on the works of theorists such as Simone de Beauvoir (1967), Clarissa Pinkola Estés (2018), Luce Irigaray (1992), Hélène Cixous (2022), Heloisa Buarque de Hollanda (2020) and Luiza Lobo (1986), among others. We assumed that the sacred feminine, a recurring archetype in the mythology of various peoples, influences a "philosophy" that centralizes and values the physical and mental aspects of the female figure, strengthening the female empowerment movement. We will also try to observe how stereotypes, images, symbols, and myths, not always of a positive nature, have crystallized in the collective imagination and have been passed on, often unconsciously, from one generation to the next, underpinning prejudices and dogmas that reinforce gender inequality. In this context, we intend to find out in which spaces the theme of the sacred feminine has been evoked in today's society and what contours the social imaginary reflects concerning femininity, as well as comparing the divergences and convergences in the lyrics of Vilela and Horta, about symbolic readings of the feminine, analyzing the movements of perenniality, derivations and wear and tear of myths, images, and symbols in the works of these poets. We assume that the result found will show that Horta and Vilela present poetic works in which resistance to the oppression experienced by women in a society in which the echoes of patriarchy resound loudly are present in a consolidated way, revealing themselves both directly and through the imaginary framework to which they resort. Although in different ways, both poets have an active voice in the daily struggle that fuels women's fight for equality and appreciation of the sacred feminine.